2018
DOI: 10.5120/ijca2018916334
|View full text |Cite
|
Sign up to set email alerts
|

A Mobile-based Tea Farming Information System

Abstract: Current trends in information and communication technology have led to emergence of smartphones with faster wireless speeds, faster graphics, better screens, and faster processors. Tapping into this technology can lead to development of mobile information systems that promote sustainable farming through timely information access, especially in tea farming. The traditional practice in tea farming has been dissemination of information through extension officers, Farmer Field Schools, mass media or farmer's shari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…They both use call centre model to disseminate agricultural information to contracted farmers [ 51 , 52 ]. Their extension services include sending bulk text messages to subscribed farmers on regular intervals to update them on weather information, pests and diseases projections, market information updates, agricultural credit services, inputs and commodities delivery services [ 19 , 52 ]. It was also found that between the two service providers, ESOKO has larger coverage and more subscribers than Farmerline [ 20 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They both use call centre model to disseminate agricultural information to contracted farmers [ 51 , 52 ]. Their extension services include sending bulk text messages to subscribed farmers on regular intervals to update them on weather information, pests and diseases projections, market information updates, agricultural credit services, inputs and commodities delivery services [ 19 , 52 ]. It was also found that between the two service providers, ESOKO has larger coverage and more subscribers than Farmerline [ 20 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Their services are offered in few local languages and are limited to specific areas and agricultural enterprises [ 51 ]. For instance, both ESOKO and Farmerline services do not cover livestock production [ 19 , 51 ]. The private sector electronic agricultural services are not accessible to all farmers due to it limitedness in services and subscription requirements.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To draw an accurate sample size to represent the tea farmers' population in the district, this study used DANIEL's methods (1999) andDANIEL et al, (2018). This method of sample size determination was previously used by other researchers (NAING et al, 2006;MUNENE AND KASAMANI, 2018). Using a 95% confidence level, 7.69% margin of error (ɛ), and 60% proportion of respondents (Ṗ), the minimum sample size was calculated as 156.…”
Section: Sampling and Data Collectionmentioning
confidence: 99%